If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) = 3(x + -4) Reorder the terms: 2(-1 + x) = 3(x + -4) (-1 * 2 + x * 2) = 3(x + -4) (-2 + 2x) = 3(x + -4) Reorder the terms: -2 + 2x = 3(-4 + x) -2 + 2x = (-4 * 3 + x * 3) -2 + 2x = (-12 + 3x) Solving -2 + 2x = -12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 2x + -3x = -12 + 3x + -3x Combine like terms: 2x + -3x = -1x -2 + -1x = -12 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + -1x = -12 + 0 -2 + -1x = -12 Add '2' to each side of the equation. -2 + 2 + -1x = -12 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = -12 + 2 -1x = -12 + 2 Combine like terms: -12 + 2 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| 5x+9(9)=71 | | -70+6x=20+3x | | 2n-12=15n-129 | | 2(4+m)=10 | | (Y^2-3y-18)(3y+15)=0 | | 3-4(7x+5)=9 | | 40-(3x+4)=2(x+6)+x | | 52.8=4.4v | | 25=11+c+(2+c) | | X+2x+11=3 | | 8x+5=5x+-7 | | 4n=4+4 | | q+50=350 | | 7x*5x-1=12*2x+2 | | 7y-1=2(y+2)-2 | | 2-19=13 | | 5n=7+8 | | 9(-187)+160= | | 36n=36 | | 0.3+x=3.75 | | 10-4y=16 | | 12-3(2x+5y)= | | 8x-47=-x+61 | | -16+11x=12+10x | | 9=4+2 | | 12m+5=m+5 | | 13-8x=9y | | 1.3z=3.25 | | -2x-204=14x+84 | | 300-50x=250+100x | | 2n+10=22 | | 2.6x=10.14 |